Determining the time of bulge formation in an elastomeric tube as it inflates, elongates and alters chemorheologically. (January 2015) - Wineman, Alan
An elastomeric cylindrical membrane with ends attached to rigid end caps is inflated and extended by a fluid that accesses its interior though one of the end caps. The membrane is at a high enough temperature that it undergoes microstructural changes due to simultaneous scission and re-crosslinking of macromolecular network junctions. Motivated by the known elastic response at lower temperatures, it is assumed that the membrane undergoes time-dependent extension and inflation. The deformation history is axially symmetric and nearly cylindrical for short times. There is then a time when a bulge-like deformation starts to form. This is treated as branching from the cylindrical deformation. For times beyond this 'branching time', the governing equations are satisfied by both the continuation of the initial deformation and the branched deformation. Criteria are derived for determining this branching time for two different assumptions about the branched response: when it is another cylindrical deformation and when it is a non-homogeneous bulge-shaped deformation.